2017
DOI: 10.1159/000484110
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Excitatory Amino Acid Transporters 1 – 3 (EAAT1, EAAT2, EAAT3) with N-Carbamoylglutamate and N-Acetylglutamate

Abstract: Background/Aims: Inborn deficiency of the N-acetylglutamate synthase (NAGS) impairs the urea cycle and causes neurotoxic hyperammonemia. Oral administration of N-carbamoylglutamate (NCG), a synthetic analog of N-acetylglutamate (NAG), successfully decreases plasma ammonia levels in the affected children. Due to structural similarities to glutamate, NCG may be absorbed in the intestine and taken up into the liver by excitatory amino acid transporters (EAATs). Methods: Using Xenopus laevis oocytes expressing eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Chacher et al (2012) reported that degradation of NCG in the rumen was approximately 18%. A previous study showed that the NCG is absorbed via excitatory AA 3 transporters into the small intestine and liver and used for Arg synthesis (Burckhardt and Burckhardt, 2017). Based on the milk yield reported in our previous study (Gu et al, 2018), approximately 0.37% of dietary NCG is transferred to the milk.…”
Section: Short Communicationmentioning
confidence: 89%
See 1 more Smart Citation
“…Chacher et al (2012) reported that degradation of NCG in the rumen was approximately 18%. A previous study showed that the NCG is absorbed via excitatory AA 3 transporters into the small intestine and liver and used for Arg synthesis (Burckhardt and Burckhardt, 2017). Based on the milk yield reported in our previous study (Gu et al, 2018), approximately 0.37% of dietary NCG is transferred to the milk.…”
Section: Short Communicationmentioning
confidence: 89%
“…A low NCG concentration (<1 μg/kg) was found in the cheese of cows from the NCG group. Burckhardt and Burckhardt (2017) reported that NCG is a watersoluble substance, which can explain why most of the NCG (~60-73%) in the milk was transferred to the whey during the cheese-making process and not stored in the cheese. In addition, the stretching and brining processes might have destroyed or extracted NCG from the curd and cheese.…”
Section: Short Communicationmentioning
confidence: 99%